Cirrhosis with ascites: Is the presence of hemorrhagic ascites an indicator of poor prognosis? - Hakan Yıldız,; Meral Akdoğan,; Nuretdin Suna,; Erkin Öztaş,; Ufuk B. Kuzu,; Zülfükar Bilge,; Onur Aydınlı,; İsmail Taşkıran, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Hemorrhagic ascites in patients with cirrhosis is described as a RBC (Red Blood cell) >50,000/mm³ and leads to increased morbidity and mortality. Positive red blood cells at a level of less than 50,000/mm³ (10,000-50,000) may be encountered in the ascites but it is not known whether this is clinically significant or not. This study aimed to examine the outcome of hemorrhagic ascites in patients with advanced cirrhosis. Materials and Methods: Data from 329 cirrhotic patients with ascites who received paracentesis at least once due to ascites was retrospectively analyzed from the period of 2007-2013 from the Türkiye Yüksek İhtisas Hospital, Department of Gastroenterology. Patients were divided according to the number of RBC, with greater than 10,000/mm³ being described as hemorrhagic ascites, and less than 10,000/mm³ described as the normal or control group. Patient data included: number of accepted intensive unit service stays, acute kidney injury (AKI), hepatic encephalopathy (HES), model for end-liver disease (MELD) score, Child Pugh score (CPS), degree of esophageal varices, spleen size and mortality rates. Results: Patients were defined as having hemorrhagic ascites with a RBC count greater than 10,000/mm³ in 118 (35.9%) patients and as a non-hemorrhagic ascites group with less than 10,000/mm³ in 211 (64.1%) patients. The hemorrhagic ascites group had advanced liver disease symptoms compared to the control group. Meld score in the hemorrhagic group was statistically higher than in the control group (21.5±8.3 vs. 17.3±6.6; p value: 0.001). The median value of bilirubin was 5.9 (0.45-33) in the hemorrhagic ascites group and 4.01 (0.39-33) in the non-hemorrhagic group (p value: 0.001). Using multivariate logistic regression analysis, hemorrhagic ascites was also an independent predictor of mortality (HR 2.7 1.4-6.3), with other mortality indicators being HCC (HR 3.1 1.5-6.4) and HRS (HR 2.6 1.2-5.5). Conclusion: Patients with hemorrhagic ascites had higher HRS, SBP and admissions to the intensive care unit. We believe that the presence of hemorrhagic ascites can be used as a marker for advanced liver disease and for predicting mortality.